Behavioural study of two hydrothermal crustacean decapods: Mirocaris fortunata and Segonzacia mesatlantica, from the Lucky Strike vent field (Mid-Atlantic Ridge). (November 2015) - Matabos, M.; Cuvelier, D.; Brouard, J.; Shillito, B.; Ravaux, J.; Zbinden, M.; Barthelemy, D.; Sarradin, P.M.; Sarrazin, J.
Abstract: Identifying the factors driving community dynamics in hydrothermal vent communities, and in particular biological interactions, is challenged by our ability to make direct observations and the difficulty to conduct experiments in those remote ecosystems. As a result, we have very limited knowledge on species׳ behaviour and interactions in these communities and how they in turn influence community dynamics. Interactions such as competition or predation significantly affect community structure in vent communities, and video time-series have successfully been used to gain insights in biological interactions and species behaviour, including responses to short-term changes in temperature or feeding strategies. In this study, we combined in situ and ex situ approaches to characterise the behaviour and interactions among two key species encountered along the Mid-Atlantic Ridge (MAR): the shrimp Mirocaris fortunata and the crab Segonzacia mesatlantica. In situ, species small-scale distribution, interactions and behaviour were studied using the TEMPO observatory module deployed on the seafloor at the base of the active Eiffel Tower edifice in the Lucky Strike vent field as part of the EMSO-Açores MoMAR observatory. TEMPO sampled 2 min of video four times a day from July 2011 to April 2012. One week of observations per month was used for 'long-term' variations, and a full video data set was analysed for January 2012. In addition, observations of crab and shrimp individuals maintained for the first time under controlled conditions in atmospheric pressure (classic tank) and pressurised (AbyssBox) aquaria allowed better characterisation and description of the different types of behaviour and interactions observed in nature. While the identified in situ spatial distribution pattern was stable over the nine months, both species displayed a significant preference for mussel bed and anhydrite substrata, and preferentially occupied the area located directly in the fluid flow axis. The aggregation behaviour of M. fortunata resulted in the occurrence of numerous intraspecific interactions mainly involving the use of two pairs of sensory organs (antenna/antennule) and fleeing behaviours when in contact or close to individuals of S. mesatlantica . The higher level of passiveness observed in the ex situ artificial environment compared to the in situ environment was attributed to the lack of stimulation related to low densities of congeners and/or of sympatric species compared to the natural environment and the absence of continuous food supply, as both species displayed a significant higher level of activity during feeding time. This result emphasises the role of food supply as a driver of species distribution and behaviour. Direct in situ observations using cameras deployed on deep-sea observatories, combined with experimental set-up in pressurised aquaria, will help investigators understand the factors influencing community dynamics and species biology at vents as well as their underlying mechanisms.